2010
DOI: 10.1094/php-2010-0820-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Distribution of Iris yellow spot virus and Thrips in Colorado Onion Fields

Abstract: Iris yellow spot virus and its onion thrips vector (Thrips tabaci) are yield limiting pests of onion in the western United States. This two-year project investigated the relationship of iris yellow spot to thrips populations, soil properties, and grower management practices in six onion fields during 2005 and 2006 in Colorado. Thrips density (average number of thrips per plant per day) was negatively associated with soil pH (r = -0.61). The incidence of iris yellow spot at harvest was positively associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Mechanical inoculation of IYSV has proven ineffective in causin onions as the transmission rate is low [77,78]. Germplasm evaluation for IYS re has relied upon field evaluations [51,55,56,[79][80][81][82][83][84][85][86]. One problem with field evalu ensuring that IYSV is present in the field and equally distributed throughout t Since mechanical inoculation is not effective in reliably producing IYS, disease ment is dependent upon thrips transmission throughout the field.…”
Section: Iris Yellow Spot and Onion Thripsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanical inoculation of IYSV has proven ineffective in causin onions as the transmission rate is low [77,78]. Germplasm evaluation for IYS re has relied upon field evaluations [51,55,56,[79][80][81][82][83][84][85][86]. One problem with field evalu ensuring that IYSV is present in the field and equally distributed throughout t Since mechanical inoculation is not effective in reliably producing IYS, disease ment is dependent upon thrips transmission throughout the field.…”
Section: Iris Yellow Spot and Onion Thripsmentioning
confidence: 99%
“…When 75 different plant introduction (PI) accessions were evaluated, plants of PIs 239633 and 546192 exhibited fewer IYS disease symptoms than plants of most accessions [53]. Other germplasm evaluations for IYS susceptibility have been conducted without a similar field layout [83][84][85][86][87].…”
Section: Iris Yellow Spot and Onion Thripsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, various production practices that could influence disease outbreaks have been identified. Based on these observations, a risk index to estimate and predict the likelihood of disease outbreaks has been developed and is being validated (Schwartz et al ., ).…”
Section: Disease Managementmentioning
confidence: 99%
“…In Allium crops, accumulation of RNA viruses in bulb used for propagation and polyphagous insect vector transmission has cardinal role in low production (Das et al, 2021;Baudry et al, 2021). Potyviruses and carlaviruses disseminated through aphid (Myzus persicae) non-persistently and favorable environmental conditions enhance the transmission rate (Perotto et al, 2014;Jayasinghe et al, 2021), while tospoviruses transmitted in persistent manner through thrips (Thrips tabaci) (Jenser & Szénási 2004;Schwartz et al, 2010;Birithia et al, 2013), and allexiviruses transmitted by (Aceria tulipae) a mite semipersistently (Dhall, 2015;Jangra et al, 2021;Mansouri et al, 2021b). Previous reports based on serological detection followed by RT-PCR showed that these viruses occurred endemically causing mixed infection demonstrated by Sevik & Akcura, (2013).…”
Section: Introductionmentioning
confidence: 99%